Root Coverage in Multiple Gingival Recessions Treated with The Tunneling Technique with Cellular Dermal Matrix vs Connective Tissue Graft: Case Reports - Rios, Yuliana; Ocampo, Natalia; Peláez, Rodrigo; García, Viviana; Zuluaga-López, Oscar H.; Chacón, Tatiana (Journal of Case Reports in Dental Medicine, 2025)
Objective: Compare the results of root coverage procedures in RT I and II gingival recessions using Acellular Dermal Matrix (ADM) vs autologous connective tissue graft (CTG).Methods: In this case series, the split-mouth technique was employed to compare the treatment outcomes of multiple bilateral RT1 gingival recessions. Tunneling surgical technique was utilized in all cases, with CTG placed in one hemi-arch and ADM used in the other.  Periodontal clinical parameters were evaluated at baseline, three, and 12 months after the surgical procedure.Results: At the 12-month follow-up, an average of 85% root coverage was achieved with CTG and 78.83% with ADM.   Complete root coverage of 60% was found with CTG and 57.90% of recessions with ADM, without statistically significant differences (p=0.394) between techniques. CTG exhibited greater clinical attachment level and probing depth with statistically significant differences (p<0.05).Conclusion: Based on the similar outcomes of both techniques, ADM can be considered as an alternative material for patients with limitations in obtaining autologous grafts.